PENGARUH LITERASI KEUANGAN, MANFAAT SHOPEEPAY LATER, DAN PENGGUNAAN SHOPEEPAYLATER TERHADAP PERILAKU KEUANGAN GENERASI Z : STUDI PADA UIN SUNAN AMPEL SURABAYA - Natasya, Syafiqah Fitri; Nawangsari, Ajeng Tita (Program Studi Akuntansi Universitas Flores, 2026)
This study examines the influence of financial literacy, perceived benefits of ShopeePayLater, and the frequency of ShopeePayLater usage on the financial behavior of Generation Z students at UIN Sunan Ampel Surabaya. The study is motivated by the rapid growth of Buy Now Pay Later (BNPL) services in Indonesia, where ShopeePayLater is the most widely used platform with an adoption rate of about 89% among e-commerce users. The rising popularity of this service among students has raised concerns about impulsive spending and default risks. According to PT Pefindo Credit Bureau (2023), from total national non-performing loans of IDR 2.12 trillion, around IDR 460 billion (21.7%) originated from Generation Z—the most active paylater users. This study applies a quantitative approach using a survey of 228 active Generation Z students at UIN Sunan Ampel Surabaya who have used ShopeePayLater. The sampling technique is purposive sampling, and data are analyzed using the Partial Least Squares (PLS) method. The results show that: (1) financial literacy positively and significantly affects financial behavior (t = 5.83; p = 0.000), indicating better management with higher literacy; (2) perceived benefits of ShopeePayLater negatively and significantly affect financial behavior (t = 3.14; p = 0.002), suggesting greater usefulness encourages consumptive behavior; and (3) ShopeePayLater usage negatively affects financial behavior (t = 4.31; p = 0.000). Theoretically, this study strengthens the Financial Literacy Framework and Technology Acceptance Model (TAM) in explaining young consumers’ financial behavior in the digital era.